Fatal Injuries Among Motorcyclists In Klang Valley, Malaysia - Nurul Kharmila Abdullah; Roszalina Ramli; Jennifer Oxley; Faridah Mohd Noor; Mohd Shah Mahmood; Abdul Karim Tajuddin; Roderick McClure (Elsevier, 2024)
Journal of Forensic and Legal Medicine Volume 26, August 2014, Pages 39-45